2014
DOI: 10.1039/c3cp55507k
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the structures and optical spectra of helical copper–silver clusters

Abstract: The structures and optical response of helical clusters ("Bernal spirals") with compositions Ag12Cu1(+) and Ag1Cu12(+) are calculated within Kohn-Sham density functional theory and the configuration interaction singles variant of time dependent density functional theory. The effects of dopant position within the cluster on the vertical excitation spectrum are investigated according to the underlying electronic structure of the major transitions. The roles of symmetry and geometry are investigated by calculatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The TDDFT calculations were performed using the atomic-orbital based NWCHEM v.6.3 package [34], based on the long range corrected LC-uPBE exchange correlation functional [35]. The def2-TZVPP basis sets were used, which can give accurate treatments of the electronics by an effective core potential (ECP) replacing 28 electrons per silver and gold atom, respectively [36]. It is reported that the LC-uPBE functional combined with def2-TZVPP basis sets can successfully reproduce the experimental photo-depletion spectroscopy of the cationic Ag and Au clusters [37].…”
Section: Computational Detailsmentioning
confidence: 99%
“…The TDDFT calculations were performed using the atomic-orbital based NWCHEM v.6.3 package [34], based on the long range corrected LC-uPBE exchange correlation functional [35]. The def2-TZVPP basis sets were used, which can give accurate treatments of the electronics by an effective core potential (ECP) replacing 28 electrons per silver and gold atom, respectively [36]. It is reported that the LC-uPBE functional combined with def2-TZVPP basis sets can successfully reproduce the experimental photo-depletion spectroscopy of the cationic Ag and Au clusters [37].…”
Section: Computational Detailsmentioning
confidence: 99%
“…50 This is not surprising since the relative position of d and s bands in Cu is more similar to gold than to silver. Exotic helical Ag-Cu 13-atom clusters have also been studied at the TDDFT level 54 finding that both the structure and the position of the Cu single atom dopant appreciably influenced the optical spectrum.…”
Section: Alloy Nanostructures In a Non-strongly Interacting Environmentmentioning
confidence: 99%
“…24,32,33 However, the spectra turn out to be rather sensitive even to rather subtle changes of the geometries. [6][7][8][9]23,24,26,[34][35][36][37][38][39] Using pseudopotentials and / or localized orbitals, the atomistic inhomogeneity of the metals can fully be taken into account. In recent years, calculations of intermediate-size noble metal clusters have been carried out using, in particular, time-dependent density-functional theory.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, calculations for intermediate-size noble metal clusters have been carried out using, in particular, time-dependent density-functional theory. [6][7][8][9]23,24,26,[34][35][36][37][38][39] Using pseudopotentials and/or localized orbitals, the atomistic inhomogeneity of the metals can fully be taken into account. Moreover, the explicit description including the d electrons has become possible although the description of the contributions of the d electrons is rather sensitive to the functionals used.…”
Section: Introductionmentioning
confidence: 99%